2002
DOI: 10.1007/s00259-002-0861-y
|View full text |Cite
|
Sign up to set email alerts
|

[18F]FDG in childhood lymphoma: clinical utility and impact on management

Abstract: Positron emission tomography (PET) with fluorine-18 fluorodeoxyglucose (FDG) is a very useful technique for the imaging of lymphomas in the adult population. It provides unique information about the behaviour of malignant cells and contributes to more accurate staging of the illness and better assessment of response to therapy. The purpose of this study was to evaluate the usefulness of FDG PET in childhood lymphoma compared with conventional imaging methods (CIMs) and clinical data. Between July 1998 and Augu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
8

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(52 citation statements)
references
References 21 publications
0
44
0
8
Order By: Relevance
“…18 F-FDG PET and PET/CT are now recognized as valuable staging procedures for most lymphoma subtypes, with a high sensitivity in patients with classic Hodgkin lymphoma and aggressive non-Hodgkin lymphoma (19). In a retrospective analysis, Montravers et al (17) found that 18 F-FDG PET was sensitive for staging and restaging of disease, showing more lesions than conventional imaging. The authors also reported high accuracies for monitoring the response to therapy and for characterizing residual masses, which occur frequently in approximately two thirds of patients with Hodgkin lymphoma and which mostly represent fibrosis rather than active disease.…”
Section: Lymphomamentioning
confidence: 99%
See 2 more Smart Citations
“…18 F-FDG PET and PET/CT are now recognized as valuable staging procedures for most lymphoma subtypes, with a high sensitivity in patients with classic Hodgkin lymphoma and aggressive non-Hodgkin lymphoma (19). In a retrospective analysis, Montravers et al (17) found that 18 F-FDG PET was sensitive for staging and restaging of disease, showing more lesions than conventional imaging. The authors also reported high accuracies for monitoring the response to therapy and for characterizing residual masses, which occur frequently in approximately two thirds of patients with Hodgkin lymphoma and which mostly represent fibrosis rather than active disease.…”
Section: Lymphomamentioning
confidence: 99%
“…Non-Hodgkin lymphoma and Hodgkin lymphoma account for about 10% and 18% of all childhood cancers, respectively; both have high cure rates (10,17,18).…”
Section: Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…Diğer görüntüleme yöntemlerinin az volümlü hastalık-larda duyarlılıklarının düşük olması, normal bü-yüklükteki lenf nodunda tümör tutulumunun gös-terilememesi, tedavi sonrası rezidü kitlede fibröz ve nekrotik doku ile aktif tümörün BT veya MRG ile ayırt edilememesi nedeni ile bu sınırlamalara fonksiyonel görüntüleme yöntemi olan 18FDG-PET üstünlük sağlamıştır ve bugün HL'nin tedavi öncesi evrelemesi, tedavisi sırasında ve tedavi bitiminden sonraki cevabın değerlendirmesinde rutin olarak kullanılmaya başlanmıştır. [18,19] Tedaviye yanıtın bilinmesi, prognozu daha iyi olan erken evrelerde daha kısa süreli ve radyoterapisiz tedavi kullanılarak geç yan etkilerin azaltıl-masına; prognozu daha kötü olan ileri evrelerde ise etkin ve daha uzun süreli tedaviler ile sağ kalımın artırılmasına olanak sağlar.…”
Section: çOcukluk çAğı Hodgkin Lenfomasında Evrelemeunclassified
“…Several investigators reported, for both pediatric HL and pediatric NHL, that additional information obtained on 18 F-FDG PET scans compared with CT scans changed management in up to 32% of patients (20,42,43). The most frequent management impact was avoiding radiotherapy of soft-tissue masses in HL, which did not show significant hypermetabolism on 18 F-FDG PET scans at the end of therapy.…”
Section: Therapy Response Assessmentmentioning
confidence: 99%